2017
DOI: 10.1073/pnas.1702482114
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism at a mimicry supergene maintained by opposing frequency-dependent selection pressures

Abstract: Explaining the maintenance of adaptive diversity within populations is a long-standing goal in evolutionary biology, with important implications for conservation, medicine, and agriculture. Adaptation often leads to the fixation of beneficial alleles, and therefore it erodes local diversity so that understanding the coexistence of multiple adaptive phenotypes requires deciphering the ecological mechanisms that determine their respective benefits. Here, we show how antagonistic frequency-dependent selection (FD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(112 citation statements)
references
References 45 publications
2
106
0
4
Order By: Relevance
“…In intraspecific trials, "close wings" behaviour was positively correlated with the outcome of the experiment, suggesting that wing closing indicates female acceptance of a courting male (coefficient = 14.3, SE of coefficient = 5.1, p = 0.0088). The other three behaviours were not significantly correlated with outcome, though all had negative coefficients and are considered rejection behaviours by other authors (Figure 2; Table 3; Chouteau et al, 2017;Jiggins, 2016…”
Section: Re Sultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In intraspecific trials, "close wings" behaviour was positively correlated with the outcome of the experiment, suggesting that wing closing indicates female acceptance of a courting male (coefficient = 14.3, SE of coefficient = 5.1, p = 0.0088). The other three behaviours were not significantly correlated with outcome, though all had negative coefficients and are considered rejection behaviours by other authors (Figure 2; Table 3; Chouteau et al, 2017;Jiggins, 2016…”
Section: Re Sultsmentioning
confidence: 74%
“…Unlike in many taxa, male choice has been much more commonly studied than female choice in Heliconius, because male choice is easier to test with model females as stimuli and because male choice is the first step in mating interactions. Female choice studies have almost exclusively documented mate preference for variation (natural or experimentally induced) in conspecific males (Chouteau, Llaurens, Piron-Prunier, & Joron, 2017;Darragh et al, 2017;Finkbeiner, Fishman, Osorio, & Briscoe, 2017). However, males still regularly court heterospecific females when they have the opportunity (Merrill, Gompert, et al, 2011) and researchers have generally found stronger assortative mating between species when there is the potential for female choice in the experimental design (Mérot, Salazar, Merrill, Jiggins, & Joron, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, multiple morphs of the same species are frequently found existing in the same locality (e.g. Brown & Benson, ; Borer et al, ), often at low densities and/or low frequencies within a population (Chouteau et al, ). Furthermore, the idea that such polymorphisms are likely to be transient and unstable has also been empirically challenged; for example, polymorphism in the poison frog Oophaga pumilio has been persistent on Bastimentos Island in Panama (Richards‐Zawacki, Yeager & Bart, ) and relaxed selection resulting from a decrease in predators produces a vastly reduced predation rate even on novel or intermediate forms (Chouteau & Angers, ).…”
Section: Theorymentioning
confidence: 99%
“…Balancing selection, mediated by negative assortative mating among inversion genotypes, prevents the fixation of the inversion, as reflected by a deficit of homozygotes for the introgressed haplotype in the wild 31 . Supergene evolution is therefore consistent with the introgressed inversion having a strong advantage under mimicry selection but being maintained in a polymorphism with ancestral haplotypes by negative frequency-dependence.…”
Section: Cc-by-nc-nd 40 International License Not Peer-reviewed) Is mentioning
confidence: 99%